(3TQW GdLOI ai GdGNJQGYGJ habG dGJaGbjI HGQjS heOi edGAeJg ddOhd GdfGejI (B/ s - (3OQhjT YHOGddg OQhjT EHQGgjes; (3SejMI eUWai GdbdjhHjs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 1992)
(3JJfGhd GdQSGdI ehVhY fbd GdJcfhdhLjG ef GdOhd GdeJbOeI Edi GdOhd GdfGejI, ehVkMG GdYbHGJ GdJj JYJQV gPg GdYedjI, eKd GdJcGdja GdYGdjI, hfOQI GdchGOQ GdYdejI, hUYhHI GdJaGhV(B. (3jTOO GdfU Ydi VQhQI GdJMhd GdJcfhdhLj chSjdI dehGLgI bVGjG GdJNda hJMbjb GdJfejI GdeSJOGeI aj GdOhd GdfGejI, eeG jSJOYj GdGHJcGQ hGdJWhjQ GdPGJj HOd GdGYJeGO Ydi GdGSJjQGO(B.s
(3CWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI, cdjI GdMbhb, bSe GdbGfhf GdJLGQj (B1992.s
(3HHdjhLQGajG(B: (3UaMGJ (B339-376.s
Keywords: (3GdbGfhf GdJLGQjs; (3GdGNJQGYs; (3GdLgO GdEHJcGQjs; (3TQW GdeTQhYjIs; (3TQW GdSQjI aj GdGNJQGYGJs; (3GdJMhd GdQbejs; (3GdeSGgeGJ s; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdJLGQjs